2005
DOI: 10.4049/jimmunol.174.4.2021
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Differentiation and Commitment of CD8+ T Cells to a Poorly Cytolytic CD8low Phenotype in the Presence of IL-4

Abstract: Exposure to IL-4 during activation of naive murine CD8+ T cells leads to generation of IL-4-producing effector cells with reduced surface CD8, low perforin, granzyme B and granzyme C mRNA, and poor cytolytic function. We show in this study that maximal development of these cells depended on exposure to IL-4 for the first 5 days of activation. Although IL-4 was not required at later times, CD8 T cell clones continued to lose surface CD8 expression with prolonged culture, suggesting commitment to the CD8low phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
87
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 53 publications
13
87
0
Order By: Relevance
“…Both CD8a and CD8b chain expression were lowered to approximately 50% of unmanipulated control mice (Fig. 1b), similar to CD8ab lo T cells generated in vitro by IL-4 exposure during antigen stimulation [19,20]. These data indicate no bias towards one co-receptor chain as observed with models of CD8aa regulatory cells [27].…”
supporting
confidence: 68%
See 3 more Smart Citations
“…Both CD8a and CD8b chain expression were lowered to approximately 50% of unmanipulated control mice (Fig. 1b), similar to CD8ab lo T cells generated in vitro by IL-4 exposure during antigen stimulation [19,20]. These data indicate no bias towards one co-receptor chain as observed with models of CD8aa regulatory cells [27].…”
supporting
confidence: 68%
“…We show that at these higher ratios, CD8 lo regulatory cells effectively deviate naive CD8 + T cell responses to HY antigen from Th1 / Tc1 to Th2 / Tc2 responses. This T cell polarization by immunoregulatory CD8 + T cells has been previously described in a variety of systems [15,20,44,45]. In particular, CD8 lo T cells were found to produce IL-4 cytokine after high avidity in vitro stimulation in the presence of .…”
supporting
confidence: 65%
See 2 more Smart Citations
“…As early as in 1993, IL-4 was found to induce ionomycin/ phorbol myristate acetate (PMA) stimulated CD8 + T cells to differentiate into non-lytic CD4 -CD8 -T cells (34). Kienzle et al also demonstrated that culturing naïve murine CD8 + T cells in the presence of IL-4 and anti-IFNγ mAb led to the generation of CD8 low cells that were poorly cytolytic and expressed low levels of perforin and granzyme A, B and C (35,36).…”
Section: Endogenous Il-4 Deviates Host Immune Response To An Ineffectmentioning
confidence: 95%